The New Ordoliberalism: A case for UBI? - Bianca Blum; Marcel Franke; Elina Malmberg; Bernhard Neumärker; Jette Weinel (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2023)
This article presents and discusses New Ordoliberalism, implemented though the introduction of Universal Basic Income, as such an alternative approach within economic policy to handle the global challenges of the 21th century, like increasing inequality. New Ordoliberalism develops the basic ideas of traditional Ordoliberalism as well as constitutional economics further by considering both ex-ante aspects of justice on the constitutional level but also incorporates concepts of justice in the outcomes in the post-constitutional level. The article discusses New Ordoliberalism from a standpoint of a paradigm shift regarding normative assumptions in society, and presents applications of New Ordoliberalism and UBI within game theory and in a model comparing the individual utility of UBI with means-tested social security system.
Keywords: 330